The modificated by the dye polimeric ionites in the hybrid spectroscopic methods of analysis - Kostenko, Elizaveta (My University, 2005)
The conditions of the immobilization dyes at the surface АВ-178 and КУ-28 were found. The interaction of Cu (II), Pb (II), Zn (II), Hg (II), Fe (III), Sn (IV), Zr (IV), Ti (IV) with the surface reagents was studied. The optimum conditions of the reactions, quantitative characteristics of the composition and the surface compounds stability; the effective dates of the modified sorbents have been obtained. A new solid-phase spectrophotometric procedures was developed for determination of the metal iones in the food objects.Визначені умови іммобілізації барвників на поверхні АВ-178 та КУ-28. Досліджена взаємодія Cu (II), Pb (II), Zn (II), Hg (II), Fe (III), Sn (IV), Zr (IV), Ti (IV) з отриманими твердофазними реагентами. Визначені: оптимальні умови реакцій, кількісні характеристики складу і стійкості поверхневих комплексів; показники ефективності іонообмінників з іммобілізованими барвниками. Розроблений ряд нових твердофазно-спектрофотометричних методик визначення металів у харчових об´єктах. Установлены условия иммобилизации красителей на поверхности АВ-178 и КУ-28. Изучено взаимодействие Cu (II), Pb (II), Zn (II), Hg (II), Fe (III), Sn (IV), Zr (IV), Ti (IV) с полученными твердофазными реагентами. Определены: оптимальные условия реакций, количественные характеристики состава и прочности образующихся на поверхности комплексов; показатели эффективности ионообменников с иммобилизованными красителями. Разработан ряд новых твердофазно-спектрофотометрических методик для определения ионов металлов в пищевых объектах.
Keywords: definition the metal; immobilized dyes; фотометрія; визначення металів; іммобілізовані барвники; кафедра харчової хімії